2019
DOI: 10.1101/858100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphine differentially alters the synaptic and intrinsic properties of D1R- and D2R-expressing medium spiny neurons in the nucleus accumbens

Abstract: Exposure to opioids reshapes future reward and motivated behaviors partially by altering the functional output of medium spiny neurons (MSNs) in the nucleus accumbens shell. Here, we investigated how morphine, a highly addictive opioid, alters synaptic transmission and intrinsic excitability on dopamine D1-receptor (D1R) expressing and dopamine D2-receptor (D2R) expressing MSNs, the two main output neurons in the nucleus accumbens shell. Using wholecell electrophysiology recordings, we show, that 24 h abstinen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 102 publications
(14 reference statements)
1
13
1
Order By: Relevance
“…Both 1-and 10-14 day morphine abstinence reduce excitatory input onto D2-MSNs in the NAc shell (Graziane et al, 2016;Hearing et al, 2016;Madayag et al, 2019;McDevitt et al, 2019). In D1-MSNs, 1-day morphine abstinence has little impact on excitatory input (McDevitt et al, 2019), while 10-14 days increases GluA2 lacking AMPA receptors and excitatory drive on D1-MSNs specifically in the shell (Hearing et al, 2016;Madayag et al, 2019). Unlike the work of Hearing and colleagues, here we found adaptations in NAc core D1-MSNs.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Both 1-and 10-14 day morphine abstinence reduce excitatory input onto D2-MSNs in the NAc shell (Graziane et al, 2016;Hearing et al, 2016;Madayag et al, 2019;McDevitt et al, 2019). In D1-MSNs, 1-day morphine abstinence has little impact on excitatory input (McDevitt et al, 2019), while 10-14 days increases GluA2 lacking AMPA receptors and excitatory drive on D1-MSNs specifically in the shell (Hearing et al, 2016;Madayag et al, 2019). Unlike the work of Hearing and colleagues, here we found adaptations in NAc core D1-MSNs.…”
Section: Discussioncontrasting
confidence: 82%
“…Several recent studies have assessed how morphine abstinence alters excitatory transmission in specific NAc MSN subtypes. Both 1- and 10-14 day morphine abstinence reduce excitatory input onto D2-MSNs in the NAc shell (Graziane et al, 2016; Hearing et al, 2016; Madayag et al, 2019; McDevitt et al, 2019). In D1-MSNs, 1-day morphine abstinence has little impact on excitatory input (McDevitt et al, 2019), while 10-14 days increases GluA2 lacking AMPA receptors and excitatory drive on D1-MSNs specifically in the shell (Hearing et al, 2016; Madayag et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cocaine conditioning and/or shNPAS4 in D1-MSNs produced no significant changes in sEPSC frequency or amplitude (Figure S7C,E). Similar to prior literature on the effects of abused substances on D2-MSNs 20,56,70,71 , we observed that cocaine conditioning reduced sEPSC frequency (Figure S7D), but not amplitude (Figure S7F), in control D2-MSNs (black bars), and this reduction was abolished by shNPAS4 (Figure S7D). These data suggest that NPAS4 plays an important role in regulating drug-induced changes in excitatory synaptic transmission on D2-MSNs, but multiple glutamatergic inputs activate NAc MSNs and influence drug seeking 13,72,73 .…”
Section: Npas4 Blocks Cocaine Conditioning-induced Dendritic Spine Gr...supporting
confidence: 90%